The other Alice : the story of Alice Liddell and Alice in Wonderland - Björk, Christina, 1938- (R&S Books, 1993)
Portrays the childhood of Alice Liddell, who was the inspiration for Lewis Carroll's "Alice in Wonderland." Includes instructions for throwing a mad tea party and other games.